Using administrative data to estimate graduation rates: Challenges, Proposed solutions and their pitfalls. - Roy, Joydeep; Mishel, Lawrence (Education Policy Analysis Archives, 2008)
In recent years there has been a renewed interest in understanding the levels and trends in high school graduation in the U.S. A big and influential literature has argued that the “true” high school graduation rate remains at an unsatisfactory level, and that the graduation rates for minorities (Blacks and Hispanics) are alarmingly low. In this paper we take a closer look at the different measures of high school graduation which have recently been proposed and which yield such low estimates of graduation rates. We argue that the nature of the variables in the Common Core of Data, the dataset maintained by the U.S. Department of Education that is the main source for all of the new measures, requires caution in calculating graduation rates, and the adjustments that have been proposed often impart significant downward bias to the estimates.